Development And Validation Of A Low-Cost Dynamic Phantom For Quality Control Of Respiratory Management Systems (Revista Interdisciplinar de Pesquisa em Engenharia, 2025)
This study aims to develop and validate a cost-effective dynamic phantom designed to simulate respiratory motion for use in the quality control of management systems. The phantom was constructed using polycarbonate material and a Nema 17 motor to replicate respiratory motion. A user-friendly graphical interface was developed to configure movement patterns. A paraffin semi-sphere was incorporated to mimic breast anatomy, and its dimensions were verified for electronic equilibrium. System calibration adjusted the amplitude of the simulated respiratory motion based on the motor's step count. Repeatability and reproducibility tests were conducted for amplitude, apnea duration, and various frequencies. The density of the paraffin buildup cap was assessed using Hounsfield Units (HU) in Treatment Planning Systems. The movement calibration yielded a third-degree polynomial fit (R² = 0.999). Repeatability tests in free-breathing mode showed an average amplitude of 31.2 ± 0.17 mm, with a global relative deviation of 0.5%. Reproducibility tests revealed variances relative to the mean of less than 0.5%. In apnea mode, the maximum relative variation in movement suspension time was 0.8%. Amplitude consistency tests indicated reliable performance with variations below 0.18 mm for amplitudes above 10 mm. The paraffin cap's HU value averaged -215 ± 40, sufficient for electronic equilibrium. The developed phantom has been validated as an effective tool for conducting prescribed tests to evaluate the quality and performance of respiratory management systems. Its high precision makes it suitable for various assessments, including dosimetric evaluations and the simulation of different respiratory cycles.